Respuesta :

Answer:

[tex]y=\frac{1}{3}x^2+4x+3[/tex]

Step-by-step explanation:

we know that

The standard form of a quadratic equation is equal to

[tex]ax^{2} +bx+c[/tex]

we have

[tex]y=\frac{1}{3}(x+6)^2-9[/tex]

This is the equation of a vertical parabola written in vertex form

Expanded the quadratic equation

[tex]y=\frac{1}{3}(x^2+12x+36)-9[/tex]

Apply distributive property right side

[tex]y=\frac{1}{3}x^2+4x+12-9[/tex]

[tex]y=\frac{1}{3}x^2+4x+3[/tex] ---> quadratic equation in standard form